Valproate, Menstrual Disorder and Polycystic Ovaries - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Three patients treated with valproate for epilepsy, beginning at 16, 17, and 31 years of age, developed a reproductive disorder and are reported from the University of Oulu, Finland.